Tibia fractures managed with minimally invasive internal fixation: a case series of 20 cases - Babu S., Narendra; Dhanraj, Prashanth; Sayeed, Ehtesham Raza; Amatul Ali, Syeda Sakina (International Journal of Research in Orthopaedics, 2023)
Distal tibia fractures are frequently associated with an extensive soft tissue injury, leading to a higher risk of complications such as skin complications, infection, non-union, and eventually poor overall outcome. This study aims to measure the outcome of open/closed distal tibia fractures treated with minimally invasive internal fixation. We aim to propose an algorithm for the management of distal tibia fractures by evaluating the treatment options, outcomes, and risk factors present. This study is a case series study of all distal tibia fractures treated surgically in Kamineni Academy of Medical Sciences, LB Nagar from 2018 to 2022. Patient records were reviewed to analyze the outcomes of surgical treatment and the risk factors associated with it.